Characterisation of the Clothespin Relocation Test as a functional assessment tool. (January 2018) - Kyberd, Peter; Hussaini, Ali; Maillet, Ghislain
Method: The Clothespin Relocation Test has been adapted from an arm training tool to create an instrument to measure hand function. It is based on the time to move three clothespins from a horizontal to a vertical bar, and back. To be generally useful, the measures need to have their psychometric properties investigated. This paper measures the characteristics of an able-bodied population to gain an understanding of the underlying statistical properties of the test, in order that it can then be used to compare with different subject groups. Fifty adults (29 males, 21 females, mean age 31) were tested with five runs of three clothespins moved up and then down. Ten subjects returned twice more to observe repeatability. Results: There was a non-Gaussian range of times, from 2.5 to 7.37 s. Mean time for Up was 4.1 s, and was 4.0 s for Down, with a skew towards the faster times of 0.57 for Up and 0.97 for Down. Over the three sessions there was a small (not significant) increase in speed 4.1 ± 0.5 s first run Down to 3.5 ± 0.4 s for third. Conclusion: These initial tests confirm that it has potential to be used as a measurement of the performance of arm movement.